2006
DOI: 10.1016/j.jns.2006.05.064
|View full text |Cite
|
Sign up to set email alerts
|

MSA-C is the predominant clinical phenotype of MSA in Japan: Analysis of 142 patients with probable MSA

Abstract: We investigated the clinical features and mode of disease progression in 142 patients with probable multiple system atrophy (MSA) according to the Consensus Criteria. The subjects included 84 men and 58 women with a mean age at onset of 58.2 ± 7.1 years (range: 38-79 years). Cerebellar signs were detected in 87.3% of these patients at the time of initial examination, and were found in 95.1% of them at latest follow-up. MSA-C was diagnosed in 83.8% of the patients at their first examination.Parkinsonism was ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 39 publications
7
78
3
1
Order By: Relevance
“…For the majority of the MSA patients, parkinsonism rather than cerebellar symptoms dominated the clinical presentation. Parkinsonism was consistent with the origin of the patient population, as MSA-P is known to be more common in Western countries (16), whereas MSA-C is more frequent in Asian countries (17). The mean age of onset of disease in this MSA patient population was 59 ± 9 y, consistent with previous reports (18).…”
Section: Resultssupporting
confidence: 90%
“…For the majority of the MSA patients, parkinsonism rather than cerebellar symptoms dominated the clinical presentation. Parkinsonism was consistent with the origin of the patient population, as MSA-P is known to be more common in Western countries (16), whereas MSA-C is more frequent in Asian countries (17). The mean age of onset of disease in this MSA patient population was 59 ± 9 y, consistent with previous reports (18).…”
Section: Resultssupporting
confidence: 90%
“…In this study, the MSA-C predominance in Japan that had been reported in previous studies was confirmed [5,6]. On the other hand, some epidemiological reports from Europe and the United States have shown MSA-P predominance [13,14].…”
Section: Discussionsupporting
confidence: 87%
“…This epidemiological difference has been confirmed by other studies in each region [6,7]. The difference between MSA-C and MSA-P is the rate of motor symptom progression [8].…”
Section: Introductionsupporting
confidence: 69%
“…The patients in this study were a good representation of the Asian and Japanese MSA population and were consistent with the previous studies [35][36][37]. Our study patients were in the relatively early stages of MSA and consequently had good ADL, but the average onset age was slightly high.…”
Section: Discussionsupporting
confidence: 90%